Project-Based Learning as the Alternative for Distance Learning in Pandemic COVID-19 - Vit Ardhyantama; Chusna Apriyanti; Lina Erviana (Universitas Pendidikan Indonesia (UPI), 2020)
Distance learning during the pandemic raises many problems such as internet network limitations, bandwidth cap and fully-loaded tasks of teachers and students. This study aims to provide a theoretical illustration of project-based learning for distance learning classes. The researchers used the library method with several stages, including determining problems and research objects, collecting data, classifying and eliminating data based on needs, doing relevance checks, synthesizing findings and describing results. The analysis was conducted qualitatively based on classified data according to the research needs.. The results of the study indicate that project-based learning is suitable to be used as an alternative of distance learning during the pandemic with six aspects of considerations: 1) readiness , 2) safety, 3) monitoring, 4) thematic,